Screening adults with tuberculosis for severe illness at notification: programme experience from Gujarat, India. (27th June 2022) - Patel, Bharatkumar Hargovandas; Shewade, Hemant Deepak; Davara, Kajal Bhagavanjibhai; Mehta, Kedar Gautambhai; Modi, Bhavesh Vitthalbhai; Vyas, Monark Jitendrabhai; Murthy, Hosadurga Jagadish Deepak; Vanitha, Basavarajachar; Kumar, Ajay M V
Abstract: Background: National tuberculosis (TB) programmes in high-burden countries do not systematically assess severity at diagnosis followed by referral for inpatient care. Due to limited capacity, comprehensive assessment of all TB patients is not practical. In three districts of Gujarat (West India) in June 2021, we determined the feasibility of screening for severe illness by paramedical staff of public facilities and the burden of 'high risk for severe illness' at notification among adults (≥15 y of age) with TB. Methods: In this cross-sectional study, the screening criteria for high risk for severe illness was the presence of any one of the following: body mass index (BMI) ≤14.0 kg/m 2, BMI ≤16.0 kg/m 2 with bilateral leg swelling, respiratory rate >24/min, oxygen saturation <94% or inability to stand without support. We summarized the feasibility indicators and burden using proportion (95% confidence interval [CI]) and median, as applicable. Results: Of 626 notified adults, 87% were screened. The median time interval for screening was 3 d from notification and all indicators were collected in 97% of patients. The burden of high risk for severe illness was high, at 41.6% (95% CI 37.5 to 45.8). Conclusions: High burden and feasibility (high coverage, acceptable time interval and minimal missing data) makes a strong case for routine screening of severe illness.